Mass transfer performance of CO2 absorption into aqueous DEEA in packed columns. (August 2016) - Xu, Bin; Gao, Hongxia; Luo, Xiao; Liao, Huiying; Liang, Zhiwu
Highlights: DEEA solution absorption performance was investigated in a Sulzer DX-type structured packing column. The KG av and cyclic capacity of DEEA-CO2 system using structured packing is higher than that of the random packing column. Two experimental KG av correlation models were proposed and found to be in satisfactory agreement with experimental results. Abstract: A bench-scale absorption column packed with high efficiency Sulzer DX-type packing was used to determine the volumetric overall mass transfer coefficient (KG av ) for CO2 absorption into an aqueous solution of DEEA. The effects of the main operating parameters, such as liquid feed temperature, DEEA concentration, lean CO2 loading, liquid flow rate, CO2 partial pressure, and inert gas flow rate were examined. The results showed that DEEA concentration, CO2 lean loading, and liquid flow rate had a significant effect on KG av while inert gas flow rate had little effect. In addition, CO2 -loaded aqueous DEEA solution was observed to have a higher KG av as compared to that of aqueous MDEA solutions. Also, the performance of CO2 absorption with DEEA in structured packing in terms of KG av and cyclic capacity (Δα) were compared with the performance in a random packing column. The structured packing column performed better than the random packing column. Finally, two experimental KG av correlation models for CO2 -DEEA system were proposed and found to be in satisfactory agreement with experimental results with AAD of 8 and 3%, respectively.